Cutaneous markers of obesity - Shareef A., Raja; Prasad, P. V. S.; Kaviarasan, P. K. (International Journal of Research in Medical Sciences, 2018)
Background: The prevalence of obesity is increasing rapidly all over the world. Obesity is accompanied by increasing mortality and morbidity due to conditions such as diabetes, cardiovascular diseases and other metabolic complications. Obesity has multiple psychological impacts as well due to discrimination and bias. Cutaneous manifestations of obesity are common due to factors such as mechanical stresses, hormonal imbalances and insulin resistance. Understanding the epidemiology of cutaneous manifestations among obese individuals will aid in better patient management. Methods: A cross sectional descriptive observational study was conducted over a period of 2 years from August 2010 to August 2012 in the Dermatology outpatient Department of a tertiary care hospital. Information on socio-demographic variables such as age, gender was collected along with anthropometry and biochemical parameters. Individuals were classified based on their type of obesity and health risk assessed using waist-hip ratio. Cutaneous manifestations of obesity were assessed using appropriate methods wherever applicable. Results: The study population consisted predominantly of individuals 20 to 40 years of age. The proportion of females were twice than males. Co-existing illnesses such as diabetes, hypertension and polycystic ovarian disease were present. Only 21% of the individuals reported exercising regularly. Most individuals had mild obesity and elevated waist-hip ratio. Acanthosis nigricans was the most common cutaneous manifestation present among 95% individuals. The other common cutaneous manifestations were striae distense, acrochordons, intertrigo, dermatophytosis and folliculitis. Conclusions: The cutaneous manifestations of obesity are due to multiple factors such as mechanical stresses and hormonal imbalances. This study indicates a high prevalence of cutaneous manifestations among obese individuals. Understanding the etiopathogenesis will facilitate in screening the high-risk individuals who present with cutaneous manifestations for other underlying illnesses. In addition, management of cutaneous manifestations will prevent the cosmetic side effects among obese individuals thus limiting the psychological effects.